Neuroscience-Based Education in The Era of Artificial Intelligence: Enhancing Cognitive Development Through Adaptive Learning Technologies - Agus Nu'man; Fathor Rosi; Oyeronke Christiana Paramole (Yayasan Avicenna, 2024)
Rapid advancements in education demand technological innovations to enhance learning quality. This study explores the role of neuroscience-based education in improving students' cognitive development through adaptive learning technology in the AI era. Using a qualitative approach with a case study design, the research involved the Principal, curriculum and student affairs deputies, teachers, and students. Data were collected through observation, in-depth interviews, and documentation, then analyzed through data reduction, presentation, and conclusion. Findings reveal that neuroscience-based adaptive learning technology enhances cognitive development by addressing individual learning styles. Intelligent learning systems enable personalized education, allowing students to progress at their own pace, improving learning efficiency and effectiveness. Beyond academic skills, these technologies foster learning motivation, engagement, and outcomes. This study underscores the importance of integrating neuroscience principles into AI-driven education to support holistic cognitive development and create engaging, personalized learning experiences, offering a fresh perspective on the intersection of neuroscience, technology, and education.